Construction of R&D Collaboration Mechanism for Small and Medium Cross-Border Technology Firms: Practices of Knowledge Sharing and Technological Breakthroughs in Transregional Teams - Xu, Dujin (Innovation in Science and Technology, 2025)
Amidst the fragmentation of globalization and the decoupling of Sino-US technologies, small and medium-sized technology firms are compelled to engage in cross-border R&D through an iterative and rapid approach. However, they face the dual challenges of diminishing knowledge spillovers and amplified cultural distance. This study integrates the Knowledge-Based View (KBV) and cultural adaptation theory to propose the “Dual-Curve Collaboration Model” (DCSM). It quantifies knowledge spillovers as KSE = Shared Coverage × Encoding Degree × Absorption Capacity and transforms cultural distance into a dynamic damping coefficient CDAC. Utilizing a mixed-methods approach with longitudinal panel data from 56 firms (2019-2023), 312 team surveys, and five extreme cases, we find that a 10% increase in KSE leads to a 3.5% improvement in R&D efficiency the following year. However, a 0.1 increase in CDAC erodes one-third of this gain. Virtual rituals and bilingual technical writing can shift the U-shaped cultural adaptation trough forward by 2.7 months and reduce the damping effect by 45%. The high-collaboration configuration is characterized by “High KSE and Low CDAC and Intensive Virtual Rituals.” Failure cases, lacking a “local knowledge specialist + minority language documentation,” exhibit efficiency 62% below the average (Tang Chenghui, Qiu Peng & Dou Jianmin, 2022). Based on these findings, we develop the CRD-Mat maturity scale, a 3-6-12 intervention roadmap, and a closed-loop retesting mechanism. This provides a “green zone” anchor for government subsidies and transforms cultural adaptation from a soft requirement into a hard metric that can be procured and insured.